Desain Intervensi Program Pembelajaran Individual (PPI) Siswa Inklusi: Studi Kasus (The Intervention Design of Individualized Education Program (IEP) for Inclusive Students: Case Study at SDN) - Khoirur Rabaika, Nuril Alvin; Ayu Rizqi Mahanani, Prima; Imadatus Sa’adati, Tatik (Happiness: Journal of Psychology and Islamic Science, 2025)
SDN Sukorame 2 Kota Kediri as a favorite school of inclusions does not yet have individualized education program (IEP) for special-needs students, so inclusion students are treated as regular students. The IEP's goal is to help stunted abilities and tasks that are still difficult to perform. This research is aimed at digging into psychological conditions and designing for IEP interventions that match the needs of students made at SDN Sukorame 2 Kota Kediri. The methods used are qualitative case studies with the principal subjects of two inclusion students who have not yet received special services, as well as the support subjects of parents and teachers. Data is collected through interviews, observations, psychological assessment, and documentary studies. Studies indicate a difference in psychological conditions between subjects which are grouped into five aspects of development, those of cognitive, physical, language, emotional and personality development, and social. Based on these results, IEP intervention designs adapted to student conditions: the first subject with intellectual disability disorder (IDD) and nearsightedness is given the finger hold method, playing lego, and multisensory fernald; whereas the second subject with tunadaksa diagnostics is given modeling techniques, tokens economy, and giving responsibility.